FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA KOPERASI DI KOTA DENPASAR - Ida Ayu Nyoman Yuliastuti; Anak Agung Putu Gede Bagus Arie Susandya (PIRAMIDA, 2018)
Net income is one of the factors that affecting the growth of Koperasi (national micro finance business inIndonesia). Even if profit is not the main purpose of it business, but Koperasi needed to improve its businesscapability. This study aims to determine and analyze the effect of the number of members, owned capital, externalcapital, business volume and assets to the Sisa Hasil Usaha (SHU) in Denpasar. The research method used in thisresearch is using secondary data, which is come from financial report of Koperasi in Denpasar in 2015 to 2017.The sample was 92 collected by purposive sampling technique. Data analysis technique used in this research ismultiple linear regression analysis. The results showed that the variable owned capital, business volume andassets have a positive effect on the SHU. In contrast, total members and total assets were not significantly effecton SHU because they have a level of significance greater than 0.05.